Histological and physiological effects of Sustanon on the liver and Kidneys of male rats - Hamza, Ekhlas Abd; Rashid, Kareem Hameed (Journal of Kerbala for Agricultural Sciences, 2017)
This research on male rats was carried out to investigate the possible effects of three different doses of artificial testosterone (Sustanon) on the histology and function of liver and kidneys of adult male rats. In this experiment 48 adult male rats divided into three groups 1, 2 and 3. These groups were injected with0.05, 0.1, 0.2 mg/kg of sustanon respectively for a period of 42 days. Blood samples were collected at the end of the experiment for the determination of the levels of liver enzymes. Male rats were then dissected out, liver and kidneys were removed, weighed and fixed in 10% formalin for histological study, and 12 adult males were used in parallel to these groups as control group. The results showed that there were significant changes in the levels of liver enzymes in all treated groups in comparison with those of the control. All injected groups showed clear histological changes in the basic structure of liver and kidneys in comparison with those for control group. These changes included the increased number of hepatocytes in liver and also some distortion in renal tubules of the kidneys. Changes like cellular hyperplasia and cell degeneration were also observed in all groups of this study especially those of high doses of sustanon. It was concluded from the results of this study that the injection of sustanon at the doses of 0.05, 0.1 and 0.2 mg/ kg in adult male rats had influenced the histological structure of liver and kidneys and also the levels of liver enzymes.